The Eurosystem's agreement on Net Financial Assets (ANFA): Covert monetary financing or legitimate portfolio management? - Philipp König; Kerstin Bernoth (DIW Economic Bulletin, 2016)
As well as implementing the common monetary policy, the national central banks (NCBs) which, together with the European Central Bank (ECB) form the Eurosystem, are also responsible for performing a range of national tasks. Among other things, these include the management of their financial assets portfolios. To ensure that this function does not interfere with the implementation of the single monetary policy, the Agreement on Net Financial Assets (ANFA) limits the total net amount of financial assets (NFA) the NCBs are permitted to hold. National central bank purchases of government bonds under ANFA have led to public accusations that this was tantamount to covert monetary financing of fiscal deficits through the "printing press" by the national central banks. The present report first explains the Agreement on NetFinancial Assets and shows the volume of securities purchased by the different NCBs under ANFA. Based on this, it examines the extent to which the accusation of monetary financing may be justified. Although there have been indications of certain national banks increasing the government bond holdings on their balance sheets in recent years, this does not provide sufficient evidence of monetary financing. However, the public debate on ANFA clearly highlights the Eurosystem's lack of transparency, particularly that of the NCBs. To ensure that confidence in European monetary policy is not undermined and both transparency and communication are improved, more detailed information on the development of NCBs' balance sheets must be published more regularly.
Keywords: E52; E58; E44; 330; monetary policy; central banking; financial markets